Prosecutor’s Analysis Of The State Of Law In The Field Of Ecology And Environmental Protection - Rustam Gafurov (The American Journal of Political Science Law and Criminology, 2021)
The article reflects the significance of the analysis of the state of legality in the field of ecology and environmental protection by prosecutors, and offers proposals for its implementation.